HISTORY OF THE DEVELOPMENT OF DICTIONARIES AND THE USE OF VOCABULARY WORK IN RUSSIAN LANGUAGE CLASSES - Khodjaniyazova, A.A. (SCIENCE and SOCIETY, 2025)
The article discusses the topic of working with different types of dictionaries, the history of compiling dictionaries, studying, vocabulary work in Russian language lessons to enrich and develop Russian speech of students in schools with the national language of instruction.